Peran Kegiatan Senam Pagi dalam Kesehatan Jasmani Kelas V SD 48 Pagar Alam - Disti Ovraliya; Aisyah Putri Dea Palupi (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to analyze the role of morning exercise activities on the health and physical fitness of fifth-grade students at SD Negeri 48 Pagar alam. Morning exercise as a routine physical activity in the school environment potentially provides significant benefits to the physical development and health of elementary school-aged children. The research method used is descriptive qualitative with an observational approach. The research subjects were 28 fifth-grade students of SD Negeri 48 Pagar alam, located in Rimba Candi Village, Candi Jaya Sub-district, Dempo Tengah District. Data collection was carried out through participatory observation, structured interviews with teachers and students, and physical fitness measurements using the Indonesian Physical Fitness Test (TKJI) for children aged 10-12 years. The results showed a significant improvement in components of students' physical fitness including cardiorespiratory endurance, muscle strength, flexibility, and balance after the implementation of routine morning exercise programs for one semester. Additionally, it was identified that morning exercise activities contributed to increased learning concentration, discipline, and school enthusiasm. Several factors supporting the success of this program include support from the school, availability of adequate facilities, and active participation of teachers as role models. Meanwhile, inhibiting factors include unpredictable weather conditions, student tardiness, and limited variation in exercise movements. This research concludes that morning exercise plays a strategic role in improving the health and physical fitness of fifth-grade students at SD Negeri 48 Pagaralam, thus it is recommended to be established as a sustainable program with the development of movement variations and provision of competent instructors.